UK consensus statement on the diagnosis of inducible laryngeal obstruction in light of the COVID‐19 pandemic. Issue 12 (8th October 2020) - Haines, Jemma; Esposito, Karen; Slinger, Claire; Pargeter, Nicola; Murphy, Jennifer; Selby, Julia; Prior, Kathryn; Mansur, Adel; Vyas, Aashish; Stanton, Andrew E.; Sabroe, Ian; Hull, James H.; et al.
Abstract: Prior to the COVID‐19 pandemic, laryngoscopy was the mandatory gold standard for the accurate assessment and diagnosis of inducible laryngeal obstruction. However, upper airway endoscopy is considered an aerosol‐generating procedure in professional guidelines, meaning routine procedures are highly challenging and the availability of laryngoscopy is reduced. In response, we have convened a multidisciplinary panel with broad experience in managing this disease and agreed a recommended strategy for presumptive diagnosis in patients who cannot have laryngoscopy performed due to pandemic restrictions. To maintain clinical standards whilst ensuring patient safety, we discuss the importance of triage, information gathering, symptom assessment and early review of response to treatment. The consensus recommendations will also be potentially relevant to other future situations where access to laryngoscopy is restricted, although we emphasize that this investigation remains the gold standard.